2016
DOI: 10.12691/jfnr-4-11-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc Oxide Nanoparticles on Barrier and Mechanical Properties of EVOH Nanocomposite film Incorporating with Plasticizer

Abstract: In this study, ethylene vinyl alcohol copolymer (EVOH) nanocomposite was prepared by adding nano zinc oxide (nano-ZnO) as a filling agent and glycerol as a plasticizer. In the solution mixing method, usually a plasticizer is used to prevent the film from becoming brittle. However, adding a plasticizer also has adverse effects on the film. Examples of such effects include; decreased barrier properties (water vapor permeability and oxygen permeability) and reduced mechanical properties (tensile strength (TS)). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The coated HSP exhibited a good ORB (130–600 s) compared with the uncoated HSP (80 s). Coatings based on SEDCFs are highly lipophilic materials, such that hygroscopic oil does not dissolve in its HSP, leading to excellent ORB 65 . The oil resistance of paper coated with different SEDCFs concentration exhibited good oil resistance as the SEDCFs concentration increased from (1–3%) due to the high hydrophobicity of it, which meets the demands for food packaging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coated HSP exhibited a good ORB (130–600 s) compared with the uncoated HSP (80 s). Coatings based on SEDCFs are highly lipophilic materials, such that hygroscopic oil does not dissolve in its HSP, leading to excellent ORB 65 . The oil resistance of paper coated with different SEDCFs concentration exhibited good oil resistance as the SEDCFs concentration increased from (1–3%) due to the high hydrophobicity of it, which meets the demands for food packaging.…”
Section: Resultsmentioning
confidence: 99%
“…The oil resistance of paper coated with different SEDCFs concentration exhibited good oil resistance as the SEDCFs concentration increased from (1–3%) due to the high hydrophobicity of it, which meets the demands for food packaging. Several studies were reported, the addition of active materials as coated part enhance their ORB as cellulose nanofibers/chitosan nanoparticles 65 , HSP/ZnO/SiO2 58 and HSP/Microcrystalline Wax Emulsion 66 .…”
Section: Resultsmentioning
confidence: 99%